Long-term effects of SARS-CoV-2 infection in hospitalized children: findings from an Italian single-center study - Valeria Calcaterra; Veronica Maria Tagi; Enza D’Auria; Alessia Lai; Sara Zanelli; Chiara Montanari; Elia Maria Biganzoli; Giuseppe Marano; Elisa Borghi; Valentina Massa; Agostino Riva; Gianvincenzo Zuccotti (Italian Journal of Pediatrics, 2024)
Abstract Background Limited evidence exists regarding the association between COVID-19 and Long COVID manifestations in children, particularly concerning variants of concern (VOCs). We aimed to characterize a cohort of pediatric patients hospitalized with confirmed acute SARS-CoV-2 and monitor them for Long COVID symptoms. Additionally, it seeks to explore any potential correlations between VOCs and clinical symptoms. Methods We conducted a prospective study involving children hospitalized from November 2021 to March 2023, with confirmed acute SARS-CoV-2 infection. A telephone survey was conducted at 3-6-12 months after discharge. Results We included 167 patients (77 F/90 M). Upon hospital admission, 95.5% of patients presented as symptomatic. Regarding patients for whom it was feasible to determine the SARS-CoV-2 variant (n = 51), the Delta variant was identified in 11 children (21.6%) and Omicron variant in the remaining 40 patients (78.4%: 27.5% BA.1 variant; 15% BA.2 variant; 57.5% BA.5 variant). 19 patients (16.5%) reported experiencing at least one symptom indicative of Long COVID (weight loss 31.6%, inappetence 26.3%, chronic cough 21.1%, fatigue 21.1%, and sleep disturbances, wheezing, abdominal pain and mood disorders 15.8%). In only 4 patients with Long COVID we could identified a specific SARS-CoV-2 variant (3 Omicron: 2 BA.1 and 1 BA.2; 1 Delta). Conclusions this study underscores that long COVID is a significant concern in the pediatric population. Our data reinforce the importance of continuously monitoring the impact of long-COVID in infants, children, and adolescents. A follow-up following SARS-CoV-2 infection is therefore advisable, with symptom investigation tailored to the patient’s age.